Choco King / Ili Farhana Hasdi ... [et al.] - Hasdi, Ili Farhana; Norisham, Nur Syamimi; Mat Zul, Ain Alia Arissa; Azhar, Fatin Azhan; Abdul Razak, Nurul Muyassarah; Muhammad Al' Munawir, Nur Alia Nadia (2021)
Mrs Futiq started this Choco king business in 2020 in Johor. She has entrepreneurial abilities such as optimism, independence, and self-confidence. This Choco King business has been recognized as Futiq Solution Sdn Bhd and has been operating in 2020. She started this business because of she is having a desire in the business. Because now many people are attracted to snacks, so she sells the Choco King. The products sold were made by her and her assistants. The main problems she always faces are costing, marketing, and packaging. Therefore, the solution we propose is to upgrade the packaging from plastic to goodies bags, make more sales and make promotions that attract buyers. Among these solutions, we recommend the best solution to the owner which is to improve to further increase the sales of her business.